2018
DOI: 10.5114/fn.2018.74659
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-223 regulates ischemic neuronal injury by targeting the type 1 insulin-like growth factor receptor (IGF1R)

Abstract: Cerebral ischemia injury seriously endangers human health and its molecular mechanism is still not fully understood. has been reported to be involved in many physiological functions but the specific role of miRNA-223 in ischemic neuronal injury is still unclear. An oxygen-glucose deprivation and simulated reperfusion (OGD/R) model was constructed here to investigate the possible role miR-223 played in ischemic neuronal injury. The expression of miRNA-223 in the OGD/R model and its effect on cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…The biological function of FGD5-AS1 in stroke remains unclear. In our present study, FGD5-AS1 is predicted and demonstrated as a ceRNA for miR-223, which has been reported to involve in OGD/R-induced neurons injury by regulat- ing IGF1R [5]. The expression of miR-223 was negatively regulated by FGD5-AS1 as we found that overexpression of FGD5-AS1 significantly decreases the level of miR-223.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…The biological function of FGD5-AS1 in stroke remains unclear. In our present study, FGD5-AS1 is predicted and demonstrated as a ceRNA for miR-223, which has been reported to involve in OGD/R-induced neurons injury by regulat- ing IGF1R [5]. The expression of miR-223 was negatively regulated by FGD5-AS1 as we found that overexpression of FGD5-AS1 significantly decreases the level of miR-223.…”
Section: Discussionsupporting
confidence: 67%
“…In our previous study, the involvement of miR-223/IGF1R in OGD/R-induced neuron injury has been proved. MiR-223 was illustrated to exhibit an inhibitory effect on the prolif-eration of OGD/R-injured neurons via retarding IGF1R expression [5]. Here, lncRNA FGD5-AS1 was forecasted and verified as a ceRNA for miR-223.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations